Changes in Statistics of Malignant Neoplasms of Central Nervous System Excluding Brain (ICD-10: C70, C72) In the Lower Silesia Region of Poland in the Years 2006-2012 - Drobnik Jaroslaw; Beck Bogusław; Suslo Robert (Journal of Neurological Research And Therapy, 2017)
Epidemiological data concerning malignant neoplasms of meninges and central nervous system parts other than brain in Poland are reported to many medical databases run by various institutions and are incongruent with each other which makes their practical interpretation highly difficult. Data on registered cases of malignant neoplasms of meninges (C70-C70.9 ICD-10) and of spinal cord, cranial nerves and parts of central nervous system other than brain (C72-C72.9 ICD-10) in the years 2006-2012, made available by public healthcare insurance provider Narodowy Fundusz Zdrowia in Lower Silesia region of Poland (NFZ) and data on new cases from Polish national neoplasms registry Krajowy Rejestr Nowotworow (KRN), were analyzed. The study revealed that those neoplasms are rare in Lower Silesia region of Poland population, number of new cases dropped in the analyzed period, but the NFZ/KRN cases ratio increased significantly especially in case of malignant neoplasms of central nervous system parts other than brain or meninges, which suggests big, and increasing with time, amount of medical procedures needed by those patients. It points at the need of respective adjustment of the level of public financing of treatment of malignant neoplasms of meninges and other central nervous system parts than brain. The study results indicate also that epidemiological reporting system in Poland shall be improved as there is growing number of Polish physicians who report mainly unspecific broad ICD-10 categories and there are year-to-year alternations of reported numbers of cases that do not have any explanation other than formal shifting in reported ICD-10 categories.
Keywords: malignant neoplasm